Potential effects of lingual fats on airway flow dynamics and particle deposition. Issue 3 (3rd March 2020) - Ma, Bingjie; Kourmatzis, Agisilaos; Zhao, Yongling; Yang, Runyu; Chan, Hak-Kim; Salehi, Fatemeh; Cheng, Shaokoon
Abstract: Fat content on upper airway soft tissue can alter the geometry of the human pharynx, most notably by narrowing the upper airway at the level of the epiglottis. Despite the important role of the epiglottis during respiration, there is a paucity of data on how its geometry can affect airway flow dynamics in an individual. This study shows how the narrowing of the human pharynx from lingual fats can potentially change airway flow dynamics and particle deposition. The velocity flow field in four geometrically realistic upper airway models representing a pharynx with different amounts of lingual fat was simulated using computational fluid dynamics (CFD) with the baseline case validated using particle image velocimetry (PIV). The deposition of particles was also computed using a standard discrete phase model (DPM) with results showing how particle deposition is affected by the narrowing of the pharynx. Copyright © 2019 American Association for Aerosol Research